Peningkatan Hasil Belajar IPS Murid Kelas IV A SD Telkom Makassar Melalui Penggunaan Aplikasi Zoom E-Conference Berbantuan Digital Game Based Learning Wordwall - Syarifah Aeni Rahman; Muhammad Nawir; Alfini Ramdhini Dg. Lu’mu (Departement of Mathematics Education, 2023)
The problem discussed in this study is how to improve the social studies learning outcomes of students in class IV A SD Telkom Makassar through the use of zoom e-conference application assisted by digital game based learning wordwall. The purpose of this study was to improve the social studies learning outcomes of students in class IV A SD Telkom Makassar through the use of zoom e-conference application assisted by Digital Game Based Learning Wordwall. The research subjects were 24 students. This type of research is a class action research. The research procedure consists of 4 stages namely planning, action, observation, and reflection. The data collection techniques used in this study are: observation and test. The results showed that in cycle I the criteria for classical completeness was 58.33% with an average student learning outcome score of 74, increased in cycle II the criteria for classical completeness was 100% with an average student learning outcome score of 80. So that there is an increase in student learning outcomes from cycle I to cycle II. In cycle II, student learning outcomes have reached the minimum completeness criteria (KKM) set at 75. So it can be concluded that there is an increase in the average value from cycle I to cycle II by using the zoom e-conference application assisted by digital games based learning wordwall which contains students more enthusiasm and interest in paying attention to learning so that there is no need to do cycle III. Based on the results of the research that has been done, it can be concluded that the use of the zoom e-conference application assisted by digital game based learning wordwall can increase the average value of social studies learning outcomes of students in class IV A SD Telkom Makassar from 74 to 84.